2002
DOI: 10.1073/pnas.112212699
|View full text |Cite
|
Sign up to set email alerts
|

CD2 molecules redistribute to the uropod during T cell scanning: Implications for cellular activation and immune surveillance

Abstract: Dynamic binding between CD2 and CD58 counter-receptors on opposing cells optimizes immune recognition through stabilization of cell-cell contact and juxtaposition of surface membranes at a distance suitable for T cell receptor-ligand interaction. Digitized time-lapse differential interference contrast and immunofluorescence microscopy on living cells now show that this binding also induces T cell polarization. Moreover, CD2 can facilitate motility of T cells along antigen-presenting cells via a movement referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 55 publications
2
31
0
Order By: Relevance
“…57). T cells cluster their TCRs in the uropod, which is central to the cell and tied to actin structure undergoing retrograde flow (58,59). T cells exhibit frequent periods of persistent motion but with intermittent stops and turns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57). T cells cluster their TCRs in the uropod, which is central to the cell and tied to actin structure undergoing retrograde flow (58,59). T cells exhibit frequent periods of persistent motion but with intermittent stops and turns.…”
Section: Discussionmentioning
confidence: 99%
“…3 and SI Appendix, Figs. S4 and S9) (59,60). Stresses were applied experimentally via loading through our optical trap system, delivering, on average, ∼10 pN per TCR-pMHC interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, USF overexpression has been found to inhibit growth in a number of cancer cell lines (27,28). USF-1 regulates CD2 expression in T cells (29) and is involved in such diverse functions as adhesion (30), scanning (31), activation (32,33), and positive/negative selection (34).…”
mentioning
confidence: 99%
“…The Joslin Clinic investigators noted that investigators at the Steno Memorial Hospital in Denmark reported a diminishing risk for ESRD over time in a similar group of patients with type 1 diabetes. 9,10 The factors responsible for this disparity are uncertain, although the pre-ESRD mortality in the Steno cohort was much higher than in the other two cohorts.…”
mentioning
confidence: 99%
“…This interaction at the site of cell-to-cell contact is called a virologic synapse with polarized T cells forming a protrusion called uropod, which mediates contact with the other cell. 9,10 Chen et al, 11 in this issue of JASN, describe similar interactions between infected T cells and renal tubular epithelia. These investigators in their in vitro experimental model found viral transmission from infected T cells to renal tubular epithelial cells through cell-to-cell interaction, which they argue occurs through the formation of a virologic synapse.…”
mentioning
confidence: 99%